2016
DOI: 10.1186/s13027-016-0106-5
|View full text |Cite
|
Sign up to set email alerts
|

Changing Patterns of lung, liver, and head and neck non-AIDS-defining cancers relative to HIV status in Tanzania between 2002-2014

Abstract: BackgroundTanzania, like other low-income countries, has an increasing cancer burden that remains underestimated. Infection-associated malignancies, particularly HIV-infection, represent a great proportion of cancer burden in Tanzania and throughout Africa. Availability of HIV treatment and improved survival of HIV patients are suggested factors related to increasing prevalence of non-AIDS-defining cancers (NADCs). This study examined patterns of NADCs and proportions of HIV-positivity at the Ocean Road Cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Cancer survival among people with HIV infection was usually described in developed countries, whereas little information is available from developing countries [84,85]. In a study conducted in Sao Paulo, Brazil, based on a probabilistic record linkage between the Cancer and the AIDS Registry, the overall survival after diagnosis of any NADC was lower in people with than without AIDS [84].…”
Section: Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer survival among people with HIV infection was usually described in developed countries, whereas little information is available from developing countries [84,85]. In a study conducted in Sao Paulo, Brazil, based on a probabilistic record linkage between the Cancer and the AIDS Registry, the overall survival after diagnosis of any NADC was lower in people with than without AIDS [84].…”
Section: Prognosismentioning
confidence: 99%
“…The disparity was mainly observed in the first year after cancer diagnosis, and was attributed to the persisting lack of national guidelines for the management of malignancies in HIV-infected people in Brazil. Especially in resourceslimited settings, therapeutic chances may be limited for subjects with HIV infection, which is often an exclusion criterion in randomized controlled trials [85].…”
Section: Prognosismentioning
confidence: 99%
“…The majority of studies that reported on mortality in this review showed that when compared with ADCs, NADCs were responsible for more cancer-related deaths in PLHIV with lung cancer being the leading cause. The incidence of lung cancer has been found to be substantially higher in PLHIV, partly due to aging and tobacco use and also because of immunosuppression and inflammatory processes associated with chronic HIV infection [ 60 , 77 , 78 ]. Another study in this review found that women with cancer and HIV-infection with lower CD4 cell counts had shorter survival when compared with their HIV-negative counterparts [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…9 10 Tanzania lacks a national population-based cancer registry and the overall dearth of proper disease surveillance and screening in the country suggests that these figures are likely deflated. 11 The few existing facility-based studies on thoracic malignancies in Tanzania likewise do not provide a complete picture on the status of thoracic malignancies in the country. 12 It is evident that the lack of diagnostic capability has made it impossible to even begin to define the state of thoracic malignancy in Tanzania and the region.…”
Section: Discussionmentioning
confidence: 99%